2018
DOI: 10.3847/1538-4357/aac6ba
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA Survey of the SCUBA-2 Cosmology Legacy Survey UKIDSS/UDS Field: Identifying Candidate z ∼ 4.5 [C II] Emitters

Abstract: We report the results of a search for serendipitous [C II] 157.74 µm emitters at z ≃ 4.4-4.7 using the Atacama Large Millimeter/submillimeter Array (ALMA). The search exploits the AS2UDS continuum survey, which covers ∼ 50 arcmin 2 of the sky towards 695 luminous (S 870 1 mJy) submillimeter galaxies (SMGs), selected from the SCUBA-2 Cosmology Legacy Survey (S2CLS) 0.96 deg 2 Ultra Deep Survey (UDS) field. We detect ten candidate line emitters, with an expected false detection rate of ten percent. All of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 111 publications
14
45
0
Order By: Relevance
“…The deconvolved FWHM source sizes of the [C II] line emission are 1.8±0.2 and 2.6±0.5 times larger than that of the continuum for SDSS J0129-0035 and SDSS J1044-0125, respectively (based on the results from imfit, Table 1). This is consistent with the results found in previous ALMA imaging of other starburst quasar host galaxies and SMGs (Wang et al 2013;Díaz-Santos et al 2016;Venemans et al 2016Venemans et al , 2017cGullberg et al 2018;Cooke et al 2018;Rybak et al 2019). In most of these systems, the [C II] emission is found to be 1.3 to >2 times more extended than that of the dust continuum emission (Gullberg et al 2018;Cooke et al 2018).…”
Section: Surface Brightnesses and Ratios Of The Resolved [C Ii] And Dsupporting
confidence: 93%
See 2 more Smart Citations
“…The deconvolved FWHM source sizes of the [C II] line emission are 1.8±0.2 and 2.6±0.5 times larger than that of the continuum for SDSS J0129-0035 and SDSS J1044-0125, respectively (based on the results from imfit, Table 1). This is consistent with the results found in previous ALMA imaging of other starburst quasar host galaxies and SMGs (Wang et al 2013;Díaz-Santos et al 2016;Venemans et al 2016Venemans et al , 2017cGullberg et al 2018;Cooke et al 2018;Rybak et al 2019). In most of these systems, the [C II] emission is found to be 1.3 to >2 times more extended than that of the dust continuum emission (Gullberg et al 2018;Cooke et al 2018).…”
Section: Surface Brightnesses and Ratios Of The Resolved [C Ii] And Dsupporting
confidence: 93%
“…• The FWHM sizes of the [C II] emission is 1.8-2.4 kpc and that of the dust continuum ∼1kpc for the two bojects, constraining the size of the intense star-forming region around the accreting SMBHs. As was found in other starburst quasar host galaxies and SMGs at high redshift, The [C II] emission regions appear to be more extended compared to that of dust continuum (Gullberg et al 2018;Cooke et al 2018).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An increase in the rest-frame peak wavelength of the dust SED with redshift is in broad agreement with observations of both individual sources (e.g. Hwang et al 2010;Swinbank et al 2014;Strandet et al 2016;Fudamoto et al 2017;Cooke et al 2018) and prior stacking analyses of mass-and SFR-selected galaxies (Magdis et al 2012;Viero et al 2013;Magnelli et al 2014;Béthermin et al 2015;Schreiber et al 2018a). Indeed, Schreiber et al (2018a) present a stacking analysis of the far-infrared emission from optically-selected "star-forming" sources (log 10 M > 9.5) that were identified across the 0.2 sq.…”
Section: Redshift Evolution In the Average Sedsupporting
confidence: 91%
“…We did not include further corrections for completeness of the surveys beyond what reported in the literature works (see Miettinen et al 2017 for a caveat for the COSMOS sources). For reference, we also report two recent results from the literature, namely number densities for ultra-red galaxies selected from the Herschel Astrophysical Terahertz Large Area Survey (H -ATLAS, Ivison et al 2016) and for a subsample of spectroscopically confirmed SMGs at z ∼ 4.5 from the S2CLS survey (Cooke et al 2018), along with the number densities originally reported in Micha lowski et al (2017). Figure 6 shows that large variations are present in the observed number densities of SMGs.…”
Section: A Conservative Lower Limit From Spectroscopymentioning
confidence: 86%